TECHNOLOGY ACCEPTANCE MODEL (TAM) UNTUK MENGANALISIS PENGGUNAAN ONLINE BANKING DI PT BANK RAKYAT INDONESIA, TBK. CABANG GIANYAR - PUTU YUDHA ASTERIA PUTRI; I Gede Nyoman Carlos Wiswanatha Mada; Putu Yudha Asteria Putri (Warmadewa Management and Business Journal (WMBJ), 2021)
This study aims to thoroughly explain the use of online banking which is influenced by the Technology Acceptance Model for customers at PT Bank Takyat Indonesia, Tbk. Gianyar Branch. The study also aims to provide consideration for the management of a bank regarding the importance of focusing attention on the use of online banking in order to improve service quality to customers. This study uses 100 customers who use online banking as the research sample. From the research objectives it can be concluded that the use of Theory Acceptance Model (TAM) which consists of perceived ease and perceived usefulness as well as computer self-efficacy at PT Bank Rakyat Indonesia, Tbk. The Gianyar branch has a positive effect on the use of online banking.